Lithium-sodium composite solid electrolyte with core-shell structure and preparation method and application thereof

By forming a sodium ion solid electrolyte shell on the surface of the lithium ion solid electrolyte, the air stability and interface stability problems of the lithium ion solid electrolyte are solved, and the long cycle performance and rate performance of lithium batteries are significantly improved.

CN116111182BActive Publication Date: 2025-04-29YIBIN NANMU NANO TECH CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202310111128.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-02-09
Publication Date
2025-04-29
Estimated Expiration
2043-02-09

AI Technical Summary

Technical Problem

Lithium-ion solid electrolytes have problems with poor air stability and poor electrochemical stability at the interface with positive and negative electrodes, resulting in poor long-cycle performance and rate performance of lithium batteries.

Method used

The lithium-ion solid electrolyte with a core-shell structure uses a core-shell structure to form a sodium ion solid electrolyte shell by atomizing and depositing the sodium ion solid electrolyte solution in a fluidized bed reactor to form a sodium ion solid electrolyte shell, thereby improving the air stability and interface stability of the lithium ion solid electrolyte.

Benefits of technology

The air stability of lithium-ion solid electrolyte and the interface stability with the positive and negative electrodes are improved, and the long cycle performance and rate performance of lithium batteries are enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116111182B_ABST
    Figure CN116111182B_ABST
Patent Text Reader

Abstract

The embodiment of the present invention relates to a lithium-sodium composite solid electrolyte with a core-shell structure and a preparation method and application thereof. The preparation method comprises: dissolving a sodium ion solid electrolyte into a solvent, stirring and dispersing, and preparing a sodium ion solid electrolyte solution; adding a lithium ion solid electrolyte into a fluidized bed reactor, so that the lithium ion solid electrolyte is in a suspended state under the action of a carrier gas; atomizing the sodium ion solid electrolyte solution and adding it into a fluidized bed reactor, and depositing and coating the sodium ion solid electrolyte on the surface of the lithium ion solid electrolyte at a first set temperature; after the solvent in the fluidized bed reactor is evaporated, taking out the lithium ion solid electrolyte coated with the sodium ion solid electrolyte, and calcining at a second set temperature to obtain a lithium-sodium composite solid electrolyte with a core-shell structure.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium battery materials, and in particular to a lithium-sodium composite solid electrolyte with a core-shell structure, and a preparation method and application thereof. Background Art

[0002] Currently, commercial lithium-ion batteries have great thermal safety risks due to the use of flammable and explosive organic electrolytes as carriers for ion transmission.

[0003] In order to further improve the safety of lithium batteries, the introduction of solid electrolyte materials with excellent intrinsic thermal safety is an effective solution. However, some lithium-ion solid electrolytes have poor air stability. When exposed to moisture in the air, residual alkali easily grows on the surface, or decomposes to produce toxic and harmful gases, which brings severe challenges to the practical application of solid electrolytes. In addition, after the solid electrolyte comes into contact with a high-voltage positive electrode or a highly reducing negative electrode such as a metallic lithium negative electrode, an interfacial reaction is likely to occur, resulting in increased interfacial impedance, loss of active lithium, and deterioration of long-cycle performance. In order to solve the above problems, the industry generally adopts technical means of surface coating and modification of lithium-ion solid electrolytes to improve their air stability and the stability of the interface with the positive and negative electrodes.

[0004] Chinese patent CN115117428A proposes a method of using atomic layer vapor deposition to coat the surface of a halide solid electrolyte with a layer of any one or at least two ceramic materials of Al2O3, SnO2, SiO2, TiO2, ZnO, ZrO2 or WO2 to improve the air stability of the solid electrolyte. However, the atomic layer vapor deposition method is expensive and difficult to use for large-scale industrial production. Moreover, coating with non-ion-conducting ceramic materials can easily lead to a decrease in the ionic conductivity of the solid electrolyte and an increase in battery polarization.

[0005] Chinese patent CN114976222A proposes using a fluidized bed to coat a layer of lithium ion oxide solid electrolyte on the outside of a sulfide solid electrolyte to improve the air stability of the sulfide and the stability when matching a metallic lithium negative electrode. However, using a lithium ion oxide solid electrolyte to coat a lithium ion sulfide solid electrolyte will result in a space charge layer effect, which will cause a change in the lithium ion concentration at the interface between the two phases, resulting in a decrease in lithium ion conductivity and a deterioration in kinetic performance. Summary of the invention

[0006] The purpose of the present invention is to provide a lithium-sodium composite solid electrolyte with a core-shell structure and a preparation method and application thereof, so as to solve the technical problems of poor air stability and poor electrochemical stability at the positive and negative electrode interfaces of lithium-ion solid electrolytes.

[0007] To this end, in a first aspect, an embodiment of the present invention provides a method for preparing a lithium-sodium composite solid electrolyte with a core-shell structure, the preparation method comprising:

[0008] Dissolving a sodium ion solid electrolyte into a solvent, stirring and dispersing, and preparing a sodium ion solid electrolyte solution;

[0009] Adding a lithium ion solid electrolyte into a fluidized bed reactor so that the lithium ion solid electrolyte is in a suspended state under the action of a carrier gas;

[0010] Atomizing a sodium ion solid electrolyte solution and adding it into a fluidized bed reactor, and allowing the sodium ion solid electrolyte to be deposited and coated on the surface of the lithium ion solid electrolyte at a first set temperature;

[0011] After the solvent in the fluidized bed reactor is evaporated to dryness, the lithium ion solid electrolyte coated with the sodium ion solid electrolyte is taken out and calcined at a second set temperature to obtain a lithium sodium composite solid electrolyte with a core-shell structure.

[0012] Preferably, the solvent includes at least one of deionized water, ethanol, acetone, isopropanol or N-methylpyrrolidone.

[0013] Preferably, the first set temperature is 60-250°C, and the second set temperature is 400-1300°C.

[0014] Further preferably, the first set temperature is 80-190°C, and the second set temperature is 600-1000°C.

[0015] In a second aspect, an embodiment of the present invention provides a core-shell structured lithium-sodium composite solid electrolyte prepared by the preparation method described in the first aspect.

[0016] Preferably, the core-shell structured lithium-sodium composite solid electrolyte comprises a lithium-ion solid electrolyte and a sodium-ion solid electrolyte layer coated on the surface of the lithium-ion solid electrolyte;

[0017] Among them, the shell thickness of the sodium ion solid electrolyte is 5nm-1um, and the diameter of the lithium-sodium composite solid electrolyte particles with the core-shell structure is 10nm-5um.

[0018] Further preferably, the shell thickness of the sodium ion solid electrolyte is 5nm-100nm, and the diameter of the lithium sodium composite solid electrolyte particles with the core-shell structure is 15nm-2um.

[0019] Preferably, the lithium ion solid electrolyte comprises Li 1+x Al x Ti 2-x (PO4)3、Li 1+y Aly Ge 2-y (PO4)3、Li 3z La 2 / 3-z TiO3、Li 7-m Ln3Z 2-m Ta m O 12 , Li 4-n Ge 1-n P n At least one of S4 or (100-p)Li2S·pP2S5, wherein 0≤x≤0.5, 0≤y≤0.5, 0<z<2 / 3, 0<m<2, 0<n<1, 10<p<60; the sodium ion solid electrolyte comprises β-Al2O3 and / or Na 1+q Zr2Si q P 3-q O 12 , where 0≤q≤3.

[0020] Further preferably, the lithium ion solid electrolyte comprises Li 1+x Al x Ti 2-x (PO4)3, Li 3z La 2 / 3-z TiO3 and Li 7-m Ln3Z 2-m Ta m O 12 Any one or more of .

[0021] In a third aspect, an embodiment of the present invention provides a battery, wherein the battery is a liquid battery or a semi-solid lithium ion battery, and any one of the positive electrode, negative electrode, separator or electrolyte of the liquid battery or semi-solid lithium ion battery comprises the lithium-sodium composite solid electrolyte with a core-shell structure described in the second aspect above; or, the battery is an all-solid-state lithium battery, and any one of the positive electrode, negative electrode or solid electrolyte of the all-solid-state lithium battery comprises the lithium-sodium composite solid electrolyte with a core-shell structure described in the second aspect above.

[0022] The method for preparing a lithium-sodium composite solid electrolyte with a core-shell structure provided by an embodiment of the present invention utilizes a sodium ion solid electrolyte shell with good air stability to improve the air stability of the lithium ion solid electrolyte and improve the interface stability with the positive and negative electrodes. In addition, the sodium ion solid electrolyte can also reduce the lithium ion migration barrier, thereby improving the kinetic performance of the lithium ion solid electrolyte. The material design is simple, and the preparation method is compatible with the production process currently used in the industry, which can greatly improve the long cycle performance and rate performance of lithium batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1A flow chart of a method for preparing a lithium-sodium composite solid electrolyte with a core-shell structure provided in an embodiment of the present invention. DETAILED DESCRIPTION

[0024] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments.

[0025] The present invention provides a method for preparing a lithium-sodium composite solid electrolyte with a core-shell structure, such as Figure 1 As shown, it mainly includes the following steps:

[0026] Step 110, dissolving a sodium ion solid electrolyte into a solvent, stirring and dispersing, and preparing a sodium ion solid electrolyte solution;

[0027] Among them, the sodium ion solid electrolyte includes β-Al2O3 and / or Na 1+q Zr2Si q P 3-q O 12 , wherein 0≤q≤3. The solvent comprises at least one of deionized water, ethanol, acetone, isopropanol or N-methylpyrrolidone.

[0028] The stirring and dispersing speed is 2000-4000 rpm.

[0029] Step 120, adding a lithium ion solid electrolyte into the fluidized bed reactor, so that the lithium ion solid electrolyte is in a suspended state under the action of a carrier gas;

[0030] Among them, lithium-ion solid electrolytes include Li 1+x Al x Ti 2-x (PO4)3、Li 1+y Al y Ge 2-y (PO4)3、Li 3z La 2 / 3- z TiO3、Li 7-m LqCy 2-m Ta m O 12 , Li 4-n Ge 1-n P n At least one of S4 or (100-p)Li2S·pP2S5, wherein 0≤x≤0.5, 0≤y≤0.5, 0<z<2 / 3, 0<m<2, 0<n<1, 10<p<60. Preferably Li 1+x Al x Ti 2-x (PO4)3, Li 3z La 2 / 3-z TiO3 and Li7-m LqCy 2-m Ta m O 12 Any one or a combination of at least two of the following.

[0031] The carrier gas can be air or nitrogen.

[0032] Step 130, atomizing the sodium ion solid electrolyte solution and adding it into a fluidized bed reactor, and depositing and coating the sodium ion solid electrolyte on the surface of the lithium ion solid electrolyte at a first set temperature;

[0033] Specifically, the first set temperature is 60-250°C, preferably 80-190°C.

[0034] Step 140, after the solvent in the fluidized bed reactor is evaporated to dryness, the lithium ion solid electrolyte coated with the sodium ion solid electrolyte is taken out, and calcined at a second set temperature to obtain a lithium sodium composite solid electrolyte with a core-shell structure.

[0035] Specifically, the second set temperature is 400-1300° C., preferably 600-1000° C. Calcination is performed in an air atmosphere, and the equipment may be a furnace body such as a muffle furnace.

[0036] The lithium-sodium composite solid electrolyte of the core-shell structure prepared by the above-mentioned preparation method of the present invention comprises a lithium-ion solid electrolyte and a sodium-ion solid electrolyte layer coated on the surface of the lithium-ion solid electrolyte. Among them, the shell thickness of the sodium-ion solid electrolyte is 5nm-1um, and the diameter of the lithium-sodium composite solid electrolyte particles of the core-shell structure is 10nm-5um. The above size design can maximize the advantages of the lithium-ion transport efficiency improvement brought by the large lattice gap of the sodium-ion solid electrolyte, and does not significantly affect other performances of the lithium-ion battery. The structure can be obtained by controlling the addition amount of the sodium-ion solid electrolyte and the lithium-ion solid electrolyte in each of the above steps. In addition, the first set temperature and the second set temperature and the calcination time will also have an impact on the material structure. Generally, for the same sodium-ion solid electrolyte material and lithium-ion solid electrolyte material, increasing the calcination temperature and reducing the calcination time are conducive to forming a lithium-sodium composite solid electrolyte with a thinner shell structure. Preferably, in the structure of the obtained material, the shell thickness of the sodium-ion solid electrolyte is 5nm-100nm, and the diameter of the lithium-sodium composite solid electrolyte particles of the core-shell structure is 15nm-2um.

[0037] The lithium-sodium composite solid electrolyte with a core-shell structure prepared by the present invention can be used as a positive electrode, a negative electrode, a separator or an electrolyte material for a liquid battery or a semi-solid lithium ion battery, or as a positive electrode, a negative electrode or a solid electrolyte material for an all-solid lithium battery.

[0038] The method for preparing a lithium-sodium composite solid electrolyte with a core-shell structure provided by an embodiment of the present invention utilizes a sodium ion solid electrolyte shell with good air stability to improve the air stability of the lithium ion solid electrolyte and improve the interface stability with the positive and negative electrodes. In addition, the sodium ion solid electrolyte can also reduce the lithium ion migration barrier, thereby improving the kinetic performance of the lithium ion solid electrolyte. The material design is simple, and the preparation method is compatible with the production process currently used in the industry, which can greatly improve the long cycle performance and rate performance of lithium batteries.

[0039] In order to better illustrate the technical solution of the present invention, the present invention is further described below through specific examples and comparative examples, but it should be understood that these examples are only used for more detailed description and should not be understood as limiting the present invention in any form, that is, they are not intended to limit the protection scope of the present invention.

[0040] Example 1

[0041] In this embodiment, a core-shell structured lithium-sodium composite solid electrolyte is prepared, wherein the core material is Li 1.3 Al 0.3 Ti 1.7 (PO4)3, the shell material is β-Al2O3, the shell thickness is 5nm, the diameter of the core-shell structure lithium sodium composite solid electrolyte is 15nm, and the preparation method is as follows:

[0042] In the first step, 30 g of β-Al2O3 was dissolved in 500 mL of deionized water and dispersed by high-speed stirring at 2500 rpm to prepare a solution.

[0043] In the second step, 10 g Li 1.3 Al 0.3 Ti 1.7 (PO4)3, making Li 1.3 Al 0.3 Ti 1.7 (PO4)3 is in a suspended state with air as the carrier gas.

[0044] In the third step, the β-Al2O3 solution was atomized and added to the fluidized bed reactor to deposit and coat the Li 1.3 Al 0.3 Ti 1.7 The surface of (PO4)3.

[0045] Step 4: After the solvent in the fluidized bed reactor is evaporated, the β-Al2O3-coated Li 1.3 Al 0.3 Ti 1.7(PO4)3 was calcined in an air atmosphere at 600°C in a muffle furnace to obtain a lithium-sodium composite solid electrolyte with a core-shell structure.

[0046] Example 2

[0047] In this embodiment, a core-shell structured lithium-sodium composite solid electrolyte is prepared, wherein the core material is Li 1.3 Al 0.3 Ge 1.7 (PO4)3, the shell material is β-Al2O3, the shell thickness is 20nm, the diameter of the core-shell structure lithium sodium composite solid electrolyte is 500nm, and the preparation method is as follows:

[0048] In the first step, 80 g of β-Al2O3 was dissolved in 2 L of ethanol and dispersed by high-speed stirring at 3000 rpm to prepare a solution.

[0049] In the second step, 500 g Li 1.3 Al 0.3 Ge 1.7 (PO4)3, making Li 1.3 Al 0.3 Ge 1.7 (PO4)3 is in a suspended state under the action of nitrogen as a carrier gas.

[0050] In the third step, the β-Al2O3 solution was atomized and added to the fluidized bed reactor to deposit and coat the Li 1.3 Al 0.3 Ge 1.7 The surface of (PO4)3.

[0051] Step 4: After the solvent in the fluidized bed reactor is evaporated, the β-Al2O3-coated Li 1.3 Al 0.3 Ge 1.7 (PO4)3 was calcined in an air atmosphere at 800°C in a muffle furnace to obtain a lithium-sodium composite solid electrolyte with a core-shell structure.

[0052] Example 3

[0053] In this embodiment, a core-shell structured lithium-sodium composite solid electrolyte is prepared, wherein the core material is Li 0.5 La 0.5 TiO3, shell material is Na 1.3 Zr2Si 0.3 P 2.7 O 12 , the shell thickness is 100nm, the diameter of the core-shell structured lithium-sodium composite solid electrolyte is 2um, and the preparation method thereof is as follows:

[0054] The first step is to mix 50g Na 1.3 Zr2Si 0.3 P 2.7 O 12 Dissolve in 1.5 L of acetone, stir and disperse at 2000 rpm to prepare a solution.

[0055] In the second step, 800 g Li 0.5 La 0.5 TiO3 makes Li 0.5 La 0.5 TiO3 is in a suspended state with air as the carrier gas.

[0056] The third step is to 1.3 Zr2Si 0.3 P 2.7 O 12 After the solution was atomized, it was added to the fluidized bed reactor and heated at 250 °C to 1.3 Zr2Si 0.3 P 2.7 O 12 Deposited and coated on Li 0.5 La 0.5 The surface of TiO3.

[0057] Step 4: After the solvent in the fluidized bed reactor is evaporated, take out the Na 1.3 Zr2Si 0.3 P 2.7 O 12 Coated Li 0.5 La 0.5 TiO3 is calcined in an air atmosphere at 1200°C in a muffle furnace to obtain a lithium-sodium composite solid electrolyte with a core-shell structure.

[0058] Example 4

[0059] In this embodiment, a core-shell structured lithium-sodium composite solid electrolyte is prepared, wherein the core material is Li 6.8 LqCy 1.8 Ta 0.2 O 12 , the shell material is Na 1.3 Zr2Si 0.3 P 2.7 O 12 , the shell thickness is 1um, the diameter of the core-shell structure lithium sodium composite solid electrolyte is 5um, and the preparation method thereof is as follows:

[0060] In the first step, 200g Na 1.3 Zr2Si 0.3 P 2.7 O 12Dissolve in 5L of isopropanol, stir and disperse at 4000rpm to prepare a solution.

[0061] In the second step, 800 g Li 6.8 LqCy 1.8 Ta 0.2 O 12 , so that Li 6.8 LqCy 1.8 Ta 0.2 O 12 With air as carrier gas, it is in a suspended state.

[0062] The third step is to 1.3 Zr2Si 0.3 P 2.7 O 12 After the solution was atomized, it was added to the fluidized bed reactor and heated at 200 °C to 1.3 Zr2Si 0.3 P 2.7 O 12 Deposited and coated on Li 6.8 LqCy 1.8 Ta 0.2 O 12 surface.

[0063] Step 4: After the solvent in the fluidized bed reactor is evaporated, take out the Na 1.3 Zr2Si 0.3 P 2.7 O 12 Coated Li 6.8 LqCy 1.8 Ta 0.2 O 12 , and calcined in an air atmosphere at 1300°C in a muffle furnace to obtain a lithium-sodium composite solid electrolyte with a core-shell structure.

[0064] Example 5

[0065] In this embodiment, a core-shell structured lithium-sodium composite solid electrolyte is prepared, wherein the core material is Li 10 GeP2S 12 The shell material is β-Al2O3, the shell thickness is 200nm, the diameter of the core-shell structure lithium-sodium composite solid electrolyte is 1um, and the preparation method is as follows:

[0066] In the first step, 200 g of β-Al2O3 was dissolved in 2.5 L of N-methylpyrrolidone and dispersed by high-speed stirring at 3500 rpm to prepare a solution.

[0067] In the second step, 750 g Li 10 GeP2S12 , so that Li 10 GeP2S 12 Under the action of nitrogen as carrier gas, it is in a suspended state.

[0068] In the third step, the β-Al2O3 solution was atomized and added to the fluidized bed reactor to deposit and coat the Li 10 GeP2S 12 surface.

[0069] Step 4: After the solvent in the fluidized bed reactor is evaporated, the β-Al2O3-coated Li 10 GeP2S 12 , and calcined in a muffle furnace at 400°C in a nitrogen atmosphere to obtain a lithium-sodium composite solid electrolyte with a core-shell structure.

[0070] Example 6

[0071] In this embodiment, a lithium-sodium composite solid electrolyte with a core-shell structure is prepared, wherein the core material is 75Li2S·25P2S5 and the shell material is Na 1.3 Zr2Si 0.3 P 2.7 O 12 , the shell thickness is 50nm, the diameter of the core-shell structured lithium-sodium composite solid electrolyte is 500nm, and the preparation method thereof is as follows:

[0072] The first step is to add 5g Na 1.3 Zr2Si 0.3 P 2.7 O 12 Dissolve in 60 mL of N-methylpyrrolidone, and disperse by stirring at 2500 rpm to prepare a solution.

[0073] In the second step, 20 g of 75Li2S·25P2S5 was added into the fluidized bed reactor, so that 75Li2S·25P2S5 was in a suspended state under the action of nitrogen as a carrier gas.

[0074] The third step is to 1.3 Zr2Si 0.3 P 2.7 O 12 After the solution was atomized, it was added to the fluidized bed reactor and heated at 60 °C to 1.3 Zr2Si 0.3 P 2.7 O 12 Deposited and coated on the surface of 75Li2S·25P2S5.

[0075] Step 4: After the solvent in the fluidized bed reactor is evaporated, take out the Na 1.3 Zr2Si0.3 P 2.7 O 12 The coated 75Li2S·25P2S5 was calcined in a muffle furnace at 600°C in a nitrogen atmosphere to obtain a lithium-sodium composite solid electrolyte with a core-shell structure.

[0076] In order to better illustrate the technical effect of the invention, we designed a comparative example according to the following method to compare with the solid electrolyte material obtained in the embodiment.

[0077] Comparative Example 1

[0078] This comparative example is the core material Li in Example 1 1.3 Al 0.3 Ti 1.7 (PO4)3.

[0079] Comparative Example 2

[0080] This comparative example is the core material Li in Example 5 10 GeP2S 12 .

[0081] The specific test comparison method is as follows:

[0082] 1. The solid electrolyte materials in Examples 1-6 and Comparative Examples 1 and 2 were subjected to air stability tests to test their initial ion conductivity and the ion conductivity after being placed in air (dew point -30°C) for 5 hours. After the solid electrolyte powder was pressed into a ceramic sheet, its electrochemical impedance spectroscopy (EIS) was tested at 25°C with carbon as the blocking electrode to calculate the lithium ion conductivity.

[0083] 2. The solid electrolyte materials in Examples 1-6 and Comparative Examples 1 and 2 were assembled into button-type liquid lithium-ion batteries for testing. The positive electrode was lithium cobalt oxide, the negative electrode was graphite, and a solid electrolyte material accounting for 5wt% of the positive electrode slurry was added during the homogenization of the positive electrode. The electrolyte was a carbonate electrolyte of 1mol / L LiPF6 dissolved in ethylene carbonate (EC) / dimethyl carbonate (DMC) in a volume ratio of 1:1. The long cycle performance was tested between 2.5V and 4.3V. The button-type battery prepared above was charged at 0.1C, 0.2C, 0.33C, 1C, and 3C rates to the charge termination voltage, and then switched to the same rate current discharge to the discharge termination voltage. Each rate was cycled 5 times to test its rate performance.

[0084] 3. The solid electrolyte materials in Examples 1-6 and Comparative Examples 1 and 2 are assembled into button-type all-solid-state lithium batteries for testing. The positive electrode is lithium cobalt oxide, the negative electrode is metallic lithium, 20wt% of solid electrolyte materials are added during the homogenization of the positive and negative electrodes, and the electrolyte is a ceramic sheet rolled from the solid electrolyte material. The long cycle performance is tested between 2.5V and 4.3V. The button-type batteries prepared above are charged at 0.1C, 0.2C, 0.33C, 1C, and 3C rates to the charge termination voltage, and then switched to the same rate current discharge to the discharge termination voltage. Each rate is cycled 5 times to test its rate performance.

[0085] The test results are shown in Table 1 below.

[0086]

[0087] Table 1

[0088] As can be seen from Table 1, compared with Comparative Examples 1 and 2, after the surface of the lithium ion solid electrolyte is coated with the sodium ion solid electrolyte, after being placed in the air for 5 hours, the decreasing trend of ion conductivity of Examples 1-6 is significantly slowed down, and the air stability is enhanced. The test results of the cycle performance and rate performance in liquid lithium ion batteries and all-solid-state lithium batteries also show that after the surface of the lithium ion solid electrolyte is coated with the sodium ion solid electrolyte, the rate performance of the battery is significantly improved, and the long cycle capacity retention rate is significantly increased.

[0089] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A method for preparing a lithium-sodium composite solid electrolyte with a core-shell structure, characterized in that: The preparation method comprises: Dissolving a sodium ion solid electrolyte into a solvent, stirring and dispersing the solution, and preparing a sodium ion solid electrolyte solution; Adding a lithium ion solid electrolyte into a fluidized bed reactor so that the lithium ion solid electrolyte is in a suspended state under the action of a carrier gas; Atomizing a sodium ion solid electrolyte solution and adding it into a fluidized bed reactor, and allowing the sodium ion solid electrolyte to be deposited and coated on the surface of the lithium ion solid electrolyte at a first set temperature; After the solvent in the fluidized bed reactor is evaporated to dryness, the lithium ion solid electrolyte coated with the sodium ion solid electrolyte is taken out and calcined at a second set temperature to obtain a lithium sodium composite solid electrolyte with a core-shell structure.

2. The preparation method according to claim 1, characterized in that: The solvent includes at least one of deionized water, ethanol, acetone, isopropanol or N-methylpyrrolidone.

3. The preparation method according to claim 1, characterized in that: The first set temperature is 60-250°C, and the second set temperature is 400-1300°C.

4. The preparation method according to claim 3, characterized in that: The first set temperature is 80-190°C, and the second set temperature is 600-1000°C.

5. A lithium-sodium composite solid electrolyte with a core-shell structure prepared by the preparation method according to any one of claims 1 to 4.

6. The lithium-sodium composite solid electrolyte with a core-shell structure according to claim 5, characterized in that: The core-shell structured lithium-sodium composite solid electrolyte comprises a lithium-ion solid electrolyte and a sodium-ion solid electrolyte layer coated on the surface of the lithium-ion solid electrolyte; Among them, the shell thickness of the sodium ion solid electrolyte is 5nm-1um, and the diameter of the lithium-sodium composite solid electrolyte particles with the core-shell structure is 10nm-5um.

7. The lithium-sodium composite solid electrolyte with a core-shell structure according to claim 6, characterized in that: The shell thickness of the sodium ion solid electrolyte is 5nm-100nm, and the diameter of the lithium sodium composite solid electrolyte particles with the core-shell structure is 15nm-2um.

8. The lithium-sodium composite solid electrolyte with a core-shell structure according to claim 6, characterized in that: The lithium ion solid electrolyte includes Li 1+x Al x Ti 2-x (PO4)3、Li 1+y Al y Ge 2-y (PO4)3、Li 3z La 2 / 3-z TiO3、Li 7-m LqCy 2-m Ta m O 12 , Li 4-n Ge 1-n P n At least one of S4 or (100-p)Li2S·pP2S5, wherein 0≤x≤0.5, 0≤y≤0.5, 0<z<2 / 3, 0<m<2, 0<n<1, 10<p<60; the sodium ion solid electrolyte comprises β-Al2O3 and / or Na 1+q Zr2Si q P 3- q O 12 , where 0≤q≤3.

9. The lithium-sodium composite solid electrolyte with a core-shell structure according to claim 8, characterized in that: The lithium ion solid electrolyte includes Li 1+x Al x Ti 2-x (PO4)3, Li 3z La 2 / 3-z TiO3 and Li 7-m Ln3Z 2-m Ta m O 12 Any one or more of .

10. A battery, characterized in that: The battery is a liquid battery or a semi-solid lithium ion battery, and any one of the positive electrode, negative electrode, separator or electrolyte of the liquid battery or semi-solid lithium ion battery comprises the lithium-sodium composite solid electrolyte with a core-shell structure as described in any one of claims 6 to 9 above; or, the battery is an all-solid-state lithium battery, and any one of the positive electrode, negative electrode or solid electrolyte of the all-solid-state lithium battery comprises the lithium-sodium composite solid electrolyte with a core-shell structure as described in any one of claims 6 to 9 above.

Citation Information

Patent Citations

  • Core-shell structure sulfide solid electrolyte, preparation method and all-solid-state battery

    CN114976222A

  • Solid electrolyte composite material with core-shell structure as well as preparation method and application of solid electrolyte composite material

    CN115117428A

  • Sodium-lithium composite solid electrolyte diaphragm, preparation method and sodium-lithium composite battery

    CN115693032A

  • Solid electrolyte and lithium ion secondary battery using the same

    JP2010118211A